2008
DOI: 10.1140/epjc/s10052-008-0772-6
|View full text |Cite
|
Sign up to set email alerts
|

Charmonium dissociation and recombination at RHIC and LHC

Abstract: Charmonium production at heavy-ion colliders is considered within the comovers interaction model. The formalism is extended by including possible secondary J/ψ production through recombination and an estimate of recombination effects is made with no free parameters involved. The comovers interaction model also includes a comprehensive treatment of initial-state nuclear effects, which are discussed in the context of such high energies. With these tools, the model properly describes the centrality and the rapidi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 57 publications
1
60
2
Order By: Relevance
“…It was fixed 130 from fits to low-energy experimental data to be σ co+J/ψ = 0.65 mb for the J/ψ and σ co+ψ(2S) = 6 mb for the ψ(2S). This value has been also successfully applied at higher energies to reproduce the RHIC 135 and LHC 136 data on J/ψ suppression in nucleus-nucleus collisions.…”
Section: 129mentioning
confidence: 99%
“…It was fixed 130 from fits to low-energy experimental data to be σ co+J/ψ = 0.65 mb for the J/ψ and σ co+ψ(2S) = 6 mb for the ψ(2S). This value has been also successfully applied at higher energies to reproduce the RHIC 135 and LHC 136 data on J/ψ suppression in nucleus-nucleus collisions.…”
Section: 129mentioning
confidence: 99%
“…On the one hand, modifications to the parton distribution functions inside the nucleus (shadowing) and other cold-nuclear-matter effects can reduce the production of quarkonia without the presence of a QGP [9,10]. On the other hand, the large number of heavy quarks produced in heavyion collisions, in particular at the energies accessible by the Large Hadron Collider (LHC), could lead to an increased production of quarkonia via statistical recombination [11][12][13][14][15][16].…”
Section: Jhep05(2012)063mentioning
confidence: 99%
“…Recently the PHENIX collaboration published new data on the J/ψ suppression in heavy ion collisions observed at RHIC [23], which have been discussed for example in [24]. These data, together with the upcoming ones from the LHC -ALICE collaboration, have encouraged us to consider, as a possible application of the determination of the X 1,2 coupling strengths, the study of the contribution of the X(3872) to the J/ψ suppression by a hot hadron gas and to revise some previous results on this topic.…”
Section: An Application To the J/ψ Suppression In Hot Hadronic Mmentioning
confidence: 99%
“…[40,41] have also considered the possibility that a recombination mechanism could compensate the J/ψ suppression due to QGP, making the drop in RHIC data less evident with respect to NA50, where this mechanism is expected to be weaker due to the much smaller energies involved. However in [24] it was shown that the recombination effects are of the same order of magnitude as the experimental uncertainties and thus they can be safely neglected.…”
Section: Comparison To Data On J/ψ Suppression At Rhicmentioning
confidence: 99%